Origin and construction of the Penitentiary of the State of Cundinamarca in the Pro-vince of Bogotá (1849-1872) - Pinzón Rivera, José Alexander (Corporación Universitaria del Caribe, CECAR., 2018)
ABSTRACT  This article gives an account of the main factors that gave rise to the project for the Bogota penitentiary. To respond to this, the reports of the time, original maps of the architects, plots and planimetric reconstructions of the spaces that formed the prison were located. The methodology used is qualitative in terms of the study of the information recovered, and quantified in relation to the materials and techniques then used. The results point to the identification of the places of the construction process and the narration of the facts between the conception of the building in 1849 and the beginning of the factory in 1872.